Superconducting Pb stripline resonators in parallel magnetic field and their application for microwave spectroscopy. (10th October 2016) - Ebensperger, Nikolaj G; Thiemann, Markus; Dressel, Martin; Scheffler, Marc
Abstract: Planar superconducting microwave resonators are key elements in a variety of technical applications and also act as sensitive probes for microwave spectroscopy of various materials of interest in present solid state research. Here superconducting Pb is a suitable material as a basis for microwave stripline resonators. To utilize Pb stripline resonators in a variable magnetic field (e.g. in ESR measurements), the electrodynamics of such resonators in a finite magnetic field has to be fully understood. Therefore we performed microwave transmission measurements (with ample applied power to work in linear response) on superconducting Pb stripline resonators in a variable, parallel magnetic field. We determined surface resistance, penetration depth, as well as real and imaginary parts, σ 1 and σ 2, of the complex conductivity of superconducting Pb as a function of a magnetic field. Here we find features reminiscent of those in temperature-dependent measurements, such as a maximum in σ 1 (coherence peak). At magnetic fields above the critical field of this type-I superconductor we still find a low-loss microwave response, which we assign to remaining superconductivity in the form of filaments within the Pb. Hysteresis effects are found in the quality factor of resonances once the swept magnetic field has exceeded the critical magnetic field. This is due to normal conducting areas that are pinned and can therefore persist in the superconducting phase. Besides zero-field-cooling we show an alternative way to eliminate these even at T < T c . Based on our microwave data, we also determine the critical magnetic field and the critical temperature of Pb in a temperature range between 1.6 K and 6.5 K and magnetic fields up to 140 mT, showing good agreement with BCS predictions. We also study a Sn sample in a Pb resonator to demonstrate the applicability of superconducting Pb stripline resonators in the experimental study of other (super-)conducting materials in a variable magnetic field.